Improving Students’ Reading Comprehension On Persuasive Text Through Storytelling - Rotua Elfrida; Sry Natalina Hutapea (The Explora, 2023)
This research deals with the improving students’ reading comprehension achievement on persuasive text through storytelling. This research is aimed to find out the improvement of the students’ reading comprehension achievement on persuasive text if teaching by applying storytelling. The design of the research is conducted by using action research method. It was done through planning, action, observation, and reflection. The subject of this research is the 2013/2014 students of the Grade XI of SMA Swa Bina Karya Medan. This research applies quantitative and qualitative method. Quantitative data are taken from the students' reading comprehension test. Qualitative data are taken from diary notes, interview, and observation. The result of the research shows that there is improvement of students’ reading comprehension on persuasive text through storytelling.